Application for Final Project Collaboration and Management in School of Applied Science, Telkom University - Hendriyanto, Robbi; Adolf Telnoni, Patrick (School of Applied Science, Telkom University, 2018)
The final project is the last stage of the students to complete the lecture. In accordance with academic rules at Telkom University allow final project work done in groups. This is to improve results more complex than the results of the final project obtained individually. But there are problems faced by students and lecturers who join the final project team, which is how to work on the final project together and monitoring the progress of each student in the team. This is due to differences in location and time in work. On the lecturer, side finds constraints that are how to be able to monitor the progress of each team member in detail. In this paper proposed a solution to overcome the problem is to apply for collaborative information technology support. The collaborative method used the Kanban's method, where each work will be divided into small parts that can be done together. Application for Final Project Collaboration and Management in School of Applied Science Telkom University was developed with Software Development Life Cycle (SDLC) Prototype method using PHP programming scripts and MySQL database. This application will manage the final project, especially in groups, facilitating the final project team to define all parts of the work of each team member who can collaborate with each other and communicate in each job. Lecturers as project supervisors can participate in collaborations and discussions in every work.